The British left and India : metropolitan anti-imperialism, 1885-1947 - Owen, Nicholas (Nicholas J.) (Oxford historical monographs., 2007)
Tracing the complex and troubled relationship between the British Left and the nationalist movement in India in the years before Indian independence, Nicholas Owen's study looks at the failure of British and Indian anti-imperialists to create the kind of powerful alliance that the Empire's governors had always feared.